Phylogenomic Characterization of SARS-CoV-2 Variants in Saudi Arabia: Insights into Viral Evolution and Transmission Dynamics: SARS-CoV-2 Variants in Saudi Arabia - Arishi, Saleh Ali; Fathy, Wael A.; Al-matary, Mohammed; Bahieldin, Ahmed; Edris, Sherif; Ramadan, Ahmed M. (Journal of Biological Insights, 2026)
Objective: The study aimed to characterize the genomic landscape of SARS-CoV-2 variants circulating in Saudi Arabia, given the country’s critical role as a global pilgrimage destination and central hub in the Middle East, to inform public health strategies and understand regional viral evolution. Methods: Ninety-four SARS-CoV-2 samples were collected from Jeddah between January and December 2022. Whole-genome sequencing was performed using the Illumina CovidSeq platform, supported by phylogenetic reconstruction (maximum likelihood), sequence alignment (Mauve), lineage assignment (Pangolin, Nextclade), and mutation profiling with emphasis on the spike gene. Results: Phylogenetic analysis revealed multiple clusters of closely related isolates, indicating limited genetic diversity and widespread local transmission. The Omicron BA.2 variant dominated (59.57%), followed by BA.1 (26.60%), while minor BA.2 sublineages indicated ongoing viral diversification. Significant mutational hotspots were observed in the spike gene (42.19%) and the ORF1ab region (35.94%), with single nucleotide variants comprising 92.31% of mutations. Key spike protein substitutions, such as D614G (98.94%) and P681H/N679K (100%), were nearly fixed and accompanied by several receptor-binding domain changes implicated in viral entry and immune evasion. Conclusion: Omicron BA.2 and its derivatives were predominant in Saudi Arabia during 2022, with mutation profiles signifying adaptive evolution under immune selection. Concentrated mutations in critical genome regions reflected ongoing adaptation to boost viral transmissibility and immune escape. These findings furnish essential baseline data for genomic surveillance and evidence-based public health policymaking in Saudi Arabia and the Middle East.